IMF conditionality : experience under stand-by and extended arrangement - International Monetary Fund.; Schadler, Susan (Washington, D.C. : International Monetary Fund, 1995)
This is part 1 of a two-volume study conducted as part of the IMF's ongoing process of evaluating its lending facilities. It focuses on IMF-supported programs and macro-economic performance during 1988 -92, reflecting information available through the end of 1993.
Includes bibliographical references: p. 51-52.
osc 16/08/2016
Loans
Keywords: International Monetary Fund; Structural adjustment (Economic policy); Conditionality (International relations)